Karakteristik Fisikokimia Mayonnaise Rendah Lemak Berbasis Isolat Protein Kedelai : Studi Formula Terbaik Berdasarkan Uji Hedonik - Elisa Tri Nursari; masrukan; Eman Darmawan; Dyah Titin Laswati (Universitas Widya Mataram, 2025)
Conventional mayonnaise is typically high in fat and cholesterol due to the use of oil and egg yolk as emulsifiers. This study aimed to develop a healthier alternative by formulating low-fat mayonnaise using soy protein isolate (SPI) as a plant-based emulsifier. The objective was to evaluate the physical and chemical properties of SPI-based mayonnaise selected through hedonic testing, and to compare it descriptively with a conventional sample (without SPI) and a commercial product. A Completely Randomized Design (CRD) was applied with five SPI concentrations: 0%, 1%, 2%, 3%, and 4%. Parameters observed included viscosity, texture, emulsion stability, color, pH, moisture, fat, and protein content. The 4% SPI formulation was identified as the most preferred based on sensory evaluation. Results showed that the 4% SPI sample had lower fat content (31.51%) and higher protein content (4.41%) than the reference samples. It also exhibited high viscosity (36,937.5 cP), good texture (0.094 N), excellent emulsion stability (96.80%), bright appearance (L=66.30; a=1.33; b=12.67), and a pH of 3.95. These findings suggest that SPI-based mayonnaise offers improved nutritional and physical qualities, making it a promising functional low-fat alternative favored by consumers.